Pengaturan Cuti Pendampingan Istri Melahirkan bagi Ayah dalam Status Pegawai Pemerintah dengan Perjanjian Kerja - Purwo Setyo Adi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The regulation of paternity leave for Contract-Based Government Employees (Pegawai Pemerintah dengan Perjanjian Kerja/PPPK) remains insufficiently and implicitly regulated within Indonesia’s civil service legal framework. This regulatory gap generates legal uncertainty and unequal protection of employment related family rights between PPPK and permanent civil servants. This study aims to examine the legal framework governing paternity leave for PPPK under existing Indonesian laws and to assess its legal implications from a normative legal perspective. The research adopts a normative legal method employing statutory and conceptual approaches. The findings demonstrate that paternity leave entitlements for PPPK are not expressly regulated and are largely subject to administrative discretion at the institutional level, thereby undermining the principles of legal certainty and equal treatment in public employment. This study underscores the urgent need for regulatory reform to explicitly recognize paternity leave as a fundamental employment right for PPPK, integrated within broader family protection policies and aligned with substantive justice in a modern rule of law state.